VD_FINDINFO Réc-civile / 2018 / 56 vom 12. Dezember 2018 - VD Tribunal cantonal (2018)
RÉCUSATION, TRANSACTION JUDICIAIRE, AUTORITÉ DE RECOURS | 6 al. 1 let. a ROTC, 47 al. 1 let. f CPC (CH), 50 al. 2 CPC (CH), 8a al. 7 CDPJ